Hubungan Riwayat Keluarga Dan Kebiasaan Merokok Dengan Kejadian Arthritis Reumaotid Di Desa Pulau Birandang Wilayah Kerja Upt Puskesmas Kampa Tahun 2022 - Midanda, Nurul Awalia; Apriyanti, Fitri; Sudiarti, Putri Eka (Journal of Engineering Science and Technology Management, 2023)
The purpose of this study was to analyze the relationship between family history and smoking habits with the incidence of rheumatoid arthritis in Pulau Birandang Village, the working area of UPT Puskesmas Kampa in 2022. The design of this study used a quantitative design with a cross sectional study design. The population in this study were 72 elderly. The sample in this study were 72 elderly. Analysis of the data used in this study is Univariate Analysis and Bivariate Analysis. From the results of research on univariate analysis, it was found that family history was in the category that had a family history of 49 people (68.1%). Respondents who smoked were in the non-smoking category as many as 39 people (54.2%) and Rheumatoid Arthritis respondents were in the Yes Rheumatoid Arthritis category as many as 39 people (54.2%). While the bivariate analysis showed that there was a relationship between family history and the incidence of rheumatoid arthritis in Pulau Birandang Village, the working area of UPT Puskesmas Kampa in 2022 and there was no relationship between smoking habits and the incidence of rheumatoid arthritis in Pulau Birandang Village, the work area of UPT Puskesmas Kampa in 2022. Results This research is expected to increase the breadth of insight, knowledge, and understanding ability of researchers and can provide skills in action regarding rheumatoid arthritis.